Theoretical Gap Analysis: Construction Of A Model Of Generation Z Consumer Behavior Towards The Adoption Of Digital Sharia Financial Services - Faricha Mulya Rahmaniah Muchsin; Mochammad Andre Agustianto (ADILLA : Jurnal Ilmiah Ekonomi Syari'ah, 2026)
Advances in financial technology have transformed the landscape of financial services, including in Islamic financial institutions, which are now developing various digital innovations such as Islamic mobile banking, halal fintech, and Sharia-compliant e-wallets. Although Generation Z is the dominant user of digital technology, their adoption rate of Islamic financial services is still relatively low. This study aims to map the theoretical gap through a Systematic Literature Review (SLR) approach, utilizing the PRISMA 2020 protocol, which examines national and international literature published between 2015 and 2025. The results of the study show that classical models such as the Technology Acceptance Model (TAM), Theory of Planned Behavior (TPB), and Unified Theory of Acceptance and Use of Technology (UTAUT) have not been able to explain the behavior of Generation Z in the context of sharia because they do not accommodate the values of trust, reputation, and religiosity. This study further formulates a new conceptual model that integrates Islamic values into the framework of digital behavior, intending to strengthen the theoretical basis for future empirical research and provide strategic direction in increasing interest, trust, and adoption rates of digital sharia financial services among Generation Z.